1970
DOI: 10.1021/bi00823a012
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of microtubule subunit protein. Effects of divalent cations, colchicine, and vinblastine

Abstract: The self-association of calf brain microtubule subunit protein (tubulin) has been studied. Divalent cations (Mg or Ca) induce the reversible aggregation of tubulin.Depending upon the divalent ion concentration, aggregation may result in an increase in sedimentation rate, formation of a 30S peak, or formation of a fibrous precipitate. Divalent cation induced precipitation is specific for the active, colchicine binding protein and is a useful step in the purification of tubulin. Colchicine alone has no apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
2
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(82 citation statements)
references
References 20 publications
2
77
2
1
Order By: Relevance
“…Currently we do not know if similar structures also occur in our assembly system that is free of accessory proteins. Earlier work has shown, however, that pure tubulin can form structures that are double rings of 26 tubulin molecules (24,25). These double rings were formed at a temperature of 20-25' in the absence of the Ca2+ chelator EGTA, and at Mg2+ concentrations similar to those we are using.…”
Section: Discussionsupporting
confidence: 71%
“…Currently we do not know if similar structures also occur in our assembly system that is free of accessory proteins. Earlier work has shown, however, that pure tubulin can form structures that are double rings of 26 tubulin molecules (24,25). These double rings were formed at a temperature of 20-25' in the absence of the Ca2+ chelator EGTA, and at Mg2+ concentrations similar to those we are using.…”
Section: Discussionsupporting
confidence: 71%
“…We have found that the presence of GTP and/or MgCI2 stabilizes colchicine binding to vinblastine-precipitated protein.7 GTP stabilization has previously been reported for microtubule protein isolated from brain.13 When vinblastineprecipitated protein is resuspended in ST, bound to 3H-colchicine, and placed in the cold for 24 hours, 85 per cent of the original binding activity is retained in the presence of GTP and/or Mg, whereas only 50 per cent of the activity remains in the absence of either or both of these factors. Although we have been unable to detect the presence of bound guanine nucleotides on vinblastine-precipitated protein, the protein will bind some 3H-GTP in vitro.…”
mentioning
confidence: 55%
“…First, we recorded the effect of pCopN on vinblastine-induced tubulin self-assembly. Vinblastine induces the formation of helical assemblies (38) by promoting tubulin-tubulin longitudinal associations (39). The size of the oligomers is large enough to be analyzed in a high speed centrifugation assay.…”
Section: Pcopn Sequesters Tubulin In a 1:1 Complex And Delaysmentioning
confidence: 99%